CORRECT CITATIONS OF THE RECENTLY DESCRIBED SPECIES OF GENERA MERODON, CHEILOSIA AND PARAGUS (DIPTERA: SYRPHIDAE) (Acta Entomologica Serbica, 2021)
The paper cites the correct citation of 14 species described in 2020, which are also listed in the Atlas of the Hoverflies of Greece. In order to prevent potential dilemmas and different taxonomic interpretations in accordance with the rules of the International Commission on Zoological Nomenclature, it is stated that 14 presented species should be cited.